A new study towards PSR J1826-1334 and PSR J1826-1256 in the region of HESS J1825-137 and HESS J1826-130 - Duvidovich, Laura Patricia (2019)
Aims. The goal of this paper is to detect synchrotron emission from the relic electrons of the crushed pulsar wind nebula (PWN) HESS J1825-137 and to investigate the origin of the γ-ray emission from HESS J1826-130. Methods. The study of HESS J1825-137 was carried out on the basis of new radio observations centred at the position of PSR J1826-1334 performed with the Karl G. Jansky Very Large Array at 1.4 GHz in configurations B and C. To investigate the nature of HESS J1826-130, we reprocessed unpublished archival data obtained with XMM-Newton. Results. The new radio continuum image towards PSR J1826-1334 reveals a bright radio source, with the pulsar located in its centre, which suggests that this feature could be the radio counterpart of the compact component of the PWN detected at high energy. The new 1.4 GHz radio data do not reveal emission with an extension comparable with that observed in γ-rays for the HESS J1825-137 source. On the other hand, the XMM-Newton study of the region including PSR J1826-1256 reveals an elongated non-thermal X-ray emitting nebula with the pulsar located in the northern border and a tail towards the peak of the very high energy source. The spectrum is characterized by a power law with a photon index going from 1.6 around the pulsar to 2.7 in the borders of the nebula, a behaviour consistent with synchrotron cooling of electrons. From our X-ray analysis we propose that HESS J1826-130 is likely produced by the PWN powered by PSR J1826-1256 via the inverse Compton mechanism.